The effectiveness of business simulation: a longitudinal study - Mohd. Hizam Hanafiah,; Mhd Suhaimi Ahmad,; Nor Liza Abdullah, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2016)
Educators, employers and policy makers have been searching for ways to help their student learn to think. In order to assist student to think and solve problems, business educators have turned to business simulation as an alternative way to develop people. Business simulation is a teaching method that can assist in developing a learning environment, which exposes students to complex situations that needs strategic decision- making. At Faculty of Economics and Business UKM, business simulation has been integrated in strategic management course as a platform for students to make management decision in a dynamic environment. A study on 120 students had been conducted to measure the effectiveness of the simulation on a longitudinal basis. Our findings show that some learning occurred in problem solving, financial management, and production management and marketing management fields. Conclusively, business simulation is a worthwhile tool to be integrated in business programs and an effective way to enhance students’ knowledge and skills.